Pediatric Craniofacial Tumor Reconstruction - Parham, Matthew J.; Ding, Yang; Wang, Daniel S.; Jiang, Austin Y.; Buchanan, Edward P. (Seminars in Plastic Surgery, 2023)
Effective management of pediatric craniofacial tumors requires coordinated input from medical, oncologic, and surgical specialties. Reconstructive algorithms must consider limitations in pediatric donor tissue and account for future growth and development. Immediate reconstruction is often focused on filling dead space, protecting underlying structures, and ensuring skeletal symmetry. Staged reconstruction occurs after the patient has reached skeletal maturity and is focused on restoring permanent dentition. Reconstructive options vary depending on the location, size, and composition of resected tissue. Virtual surgical planning (VSP) reduces the complexity of pediatric craniofacial reconstruction and ensures more predictable outcomes.
Keywords: plastic surgery; neoplasms; head and neck; reconstruction; maxillomandibular; pediatrics